Ragam Inisiatif Reformasi Pendidikan dalam Meningkatkan Kualitas dan Pemerataan Pendidikan di Wilayah Perbatasan: Refleksi dari Kabupaten Mahakam Ulu - Florianus Alui; Reza Fathurrahman (Dinasti Review, 2024)
As a border region, Mahakam Ulu Regency has homework to improve the quality and equality of education in the area. Moreover, current conditions show that the Human Development Index in Mahakam Ulu Regency is still low. With its status as a border area, the Mahakam Ulu Regency Government has a big responsibility to improve the quality and equality of education in the area, especially in the era of regional autonomy. This article aims to analyze various reform initiatives in the education sector carried out by the Mahakam Ulu Regency Government in improving the quality and equality of education as one of the border regions. This article uses a qualitative approach with the process of collecting and analyzing literature and document study data. The results of the analysis show that infrastructure development and providing educational scholarships to increase human resource capacity are the most prominent initiatives among the various strategic programs carried out by the Mahakam Ulu Regency Government as an effort to reform education in the region.